Evaluasi Demokrasi Kepemiluan Tahun 2024 Dalam Perspektif Hukum Administrasi Negara: Proses Pencalonan Wakil Presdien - Aditya Andela Pratama; Kholifatul Muna (Supremasi Hukum: Jurnal Penelitian Hukum, 2026)
State administrative law has a strategic role in realizing constitutional goals through regulating administrative procedures and actions. The 2024 elections in Indonesia reflected the application of state administrative law, but were marked by administrative polemics, particularly in the nomination of Gibran Rakabuming Raka as a vice presidential candidate. The main problem arises from the inconsistency between Constitutional Court Decision Number 90/PUU-XXI/2023 and PKPU Number 19 of 2023, which causes legal conflicts in the administrative process of registering and determining candidates. This research aims to analyze administrative violations and evaluate the validity of the determination of Gibran's candidacy based on state administrative law. The results of the study are expected to provide legal recommendations to strengthen a transparent and accountable election administration system. The results of this study show that in material terms, the General Election Commission did not make careful preparations in the registration stage, and in formal terms, there was a delay in the issuance of the Minutes of Acceptance of Registration (BAPP). Both of these are contrary to the principles of State Administrative Law. The validity of the KPU's decision also raises juridical issues due to legal defects in the inclusion of the basis for consideration of changes to the KPU Regulation (PKPU). This finding indicates a weakness in the governance of registration administration that has the potential to invalidate KPU's decision through the State Administrative Court (PTUN). This research confirms the importance of the KPU to increase the accuracy in the preparation of each stage of the election in order to maintain the credibility and legitimacy of democracy in Indonesia.